Faktor Determinan Kejadian Stunting pada Balita di Provinsi Kalimantan Barat (Studi Data Riskesdas Tahun 2018) - Agus Samsudrajat. S; Rifan Setyawan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Stunting toddlers is a chronic nutritional problem caused by many factors, such as socioeconomic conditions, maternal nutrition during pregnancy, illness in infants, and a lack of nutritional intake in infants. West Kalimantan has a high prevalence of stunting compared to the national prevalence of 36.5%. The purpose of this study was to determine the determinants associated with the incidence of stunting in West Kalimantan. This type of research uses a quantitative approach with a cross-sectional study design. The population is 2,064 people, and the sample in this study is 335 respondents by random sampling. The statistical test used was chi-squared with a 95% confidence level. The results showed that there was no relationship between PMT (p-value of 1.000), history of breastfeeding (p-value of 0.052), history of immunization (p-value of 0.640), history of infection (p-value of 0.474), and access to health services with stunting events (p-value of 0.902) in West Kalimantan. Suggestions for the government and health agencies: it is expected to increase awareness, dissemination, and information to the public regarding incomplete immunization history with a risk factor of 1.704 and a history of non-exclusive breastfeeding with a 1.326 times greater risk of influencing stunting.